Infusing intercultural awareness in English materials development for 4th grade at Islamic elementary school : English - Ivana Nabilah Qoriroh Mujahidah; Mahardika, Fajar Tri; Yutisanto, Iman; Roykhanah; Riyan, Ahmad; Sabilah, Fardini (JEES (Journal of English Educators Society), 2023)
Embedding intercultural awareness in teaching English is an essential aspect that must be considered. This paper aims to develop the English materials for 4th grade at Islamic Elementary School. The researchers employed mixed-method research to do a need analysis and design the English materials. Choosing and Analyzing the English material from the 4th grade's book was the first step in collecting the data. Then, the researchers spread the questionnaires to the 13 teachers and 71 students as the research participants that have selected purposively. The data was analyzed using explanatory sequential mixed methods, in which the qualitative data was used to explain the quantitative data results. This paper revealed that teachers and students agreed that infusing intercultural awareness is essential to learning English. They also proposed the appropriate materials to be developed with the researchers, such as adding typical food and traditional festival in the introduction materials. After designing and developing the materials, the researchers finally produced online materials in the form of video. The researchers tried to implement the video to get constructive feedback. The students' and teachers' perspectives are almost the same. HIGHLIGHTS : Infusing intercultural awareness is essential in ELT since it gained someadvantages of increasing knowledge about cultural diversity by using English. The most appropriate teaching materials, methods, and activities in ELT for 4th grade are determined by the students’ needs and teachers’ perspectives. Designing and developing English materials could enhance the quality of the teaching and learning process, whether inside or inside the classroom. Even though, there are still some challenges such as the students limitation on having English vocabularies and teachers with limited knowledge in teaching strategies.